The structure and usage of municipal property in the Pardubice region - Sobotka, Martin (Univerzita Pardubice, 2010)
The paper deals with analysis of structure of municipal property and ways of it using. Every management of property should bring to owner certain positive effects, which would contribute to achievement of objectives of owner. These objectives relate to ensurance of basic function of municipalities and support of development of municipality. Hence the relations between ways of management of property and municipal development are searched.
Keywords: development; management of property; municipality; property